Q. 225.0( 1 Vote )

# If , and , verify:(i) (AB) C = A (BC)(ii) A(B + C) = AB + AC

We have matrices A, B and C, such that   In order to multiply two matrices, A and B, the number of columns in A must equal the number of rows in B. Thus, if A is an m x n matrix and B is an r x s matrix, n = r.

(i). We need to verify: (AB)C = A(BC)

Take L.H.S = (AB)C

First, compute AB. Multiply 1st row of matrix A by matching members of 1st column of matrix B, then sum them up.

(1, 2)(2, 3) = (1 × 2) + (2 × 3)

(1, 2)(2, 3) = 2 + 6

(1, 2)(2, 3) = 8 Multiply 1st row of matrix A by matching members of 2nd column of matrix B, then sum them up.

(1, 2)(3, -4) = (1 × 3) + (2 × -4)

(1, 2)(3, -4) = 3 – 8

(1, 2)(3, -4) = -5 Similarly, let us fill for the rest of elements.   Let .

Now, compute for DC. [ (AB)C = DC] Multiply 1st row of matrix D by matching members of 1st column of matrix C, then sum them up.

(8, -5)(1, -1) = (8 × 1) + (-5 × -1)

(8, -5)(1, -1) = 8 + 5

(8, -5)(1, -1) = 13 Multiply 1st row of matrix D by matching members of 2nd column of matrix C, then sum them up.

(8, -5)(0, 0) = (8 × 0) + (-5 × 0)

(8, -5)(0, 0) = 0 + 0

(8, -5)(0, 0) = 0 Similarly, let us fill for the rest of elements.   So, Take R.H.S: A(BC)

First, compute BC. Multiply 1st row of matrix B by matching members of 1st column of matrix C, then sum them up.

(2, 3)(1, -1) = (2 × 1) + (3 × -1)

(2, 3)(1, -1) = 2 – 3

(2, 3)(1, -1) = -1 Multiply 1st row of matrix B by matching members of 2nd column of matrix C, then sum them up.

(2, 3)(0, 0) = (2 × 0) + (3 × 0)

(2, 3)(0, 0) = 0 + 0

(2, 3)(0, 0) = 0 Similarly, let us fill for the rest of the elements.   Let .

Now, compute for AE. Multiply 1st row of matrix A by matching members of 1st column of matrix E, then sum them up.

(1, 2)(-1, 7) = (1 × -1) + (2 × 7)

(1, 2)(-1, 7) = -1 + 14

(1, 2)(-1, 7) = 13 Multiply 1st row of matrix A by matching members of 2nd column of matrix E, then sum them up.

(1, 2)(0, 0) = (1 × 0) + (2 × 0)

(1, 2)(0, 0) = 0 + 0

(1, 2)(0, 0) = 0 Similarly, repeat the step for the other elements.   So, Thus, (AB)C = A(BC).

(ii). We need to verify: A(B + C) = AB + AC

Take L.H.S: A(B + C)   Let B + C = F, such that Now, multiply A and F. Multiply 1st row of matrix A by matching members of 1st column of matrix F, then sum them up.

(1, 2)(3, 2) = (1 × 3) + (2 × 2)

(1, 2)(3, 2) = 3 + 4

(1, 2)(3, 2) = 7 Multiply 1st row of matrix A by matching members of 2nd column of matrix F, then sum them up.

(1, 2)(3, -4) = (1 × 3) + (2 × -4)

(1, 2)(3, -4) = 3 – 8

(1, 2)(3, -4) = -5 Similarly, repeat the steps for the other elements.   So, Now, take R.H.S: AB + AC

Compute AB. Multiply 1st row of matrix A by matching members of 1st column of matrix B, then sum them up.

(1, 2)(2, 3) = (1 × 2) + (2 × 3)

(1, 2)(2, 3) = 2 + 6

(1, 2)(2, 3) = 8 Multiply 1st row of matrix A by matching members of 2nd column of matrix B, then sum them up.

(1, 2)(3, -4) = (1 × 3) + (2 × -4)

(1, 2)(3, -4) = 3 – 8

(1, 2)(3, -4) = -5 Similarly, repeat the steps for the other elements.   So, Now, compute AC. Multiply 1st row of matrix A by matching members of 1st column of matrix C, then sum them up.

(1, 2)(1, -1) = (1 × 1) + (2 × -1)

(1, 2)(1, -1) = 1 – 2

(1, 2)(1, -1) = -1 Multiply 1st row of matrix A by matching members of 2nd column of matrix C, then sum them up.

(1, 2)(0, 0) = (1 × 0) + (2 × 0)

(1, 2)(0, 0) = 0 + 0

(1, 2)(0, 0) = 0 Similarly, repeat the steps for the other elements.   So,  Matrices of same order can be added or subtracted.  So, clearly L.H.S = R.H.S.

Thus, A(B + C) = AB + AC.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Triangular Matrices & operations on matrices58 mins  Determinants of Matrices of different order59 mins  Types of Matrices & Properties51 mins  Determining a determinant63 mins  Know About finding the Adjoint & Inverse Of Matrix46 mins  Interactive Quiz on Properties of Determinants43 mins  Test Yourself, Properties of Determinants30 mins  Interactive Quiz on Matrices & Determinants48 mins  Lecture on Product of Determinants58 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 